8000-year monsoonal record from Himalaya revealing reinforcement of tropical and global climate systems since mid-Holocene. Issue 1 (December 2017) - Srivastava, Pradeep; Agnihotri, Rajesh; Sharma, Deepti; Meena, Narendra; Sundriyal, Y.; Saxena, Anju; Bhushan, Ravi; Sawlani, R.; Banerji, Upasana; Sharma, C.; Bisht, P.; Rana, N.; et al.
Abstract We provide the first continuous Indian Summer Monsoon (ISM) climate record for the higher Himalayas (Kedarnath, India) by analyzing a14 C-dated peat sequence covering the last 8000 years, with 50 years temporal resolution. The ISM variability inferred using various proxies reveal striking similarity with the Greenland ice core (GISP2) temperature record and rapid denitrification changes recorded in the sediments off Peru. The Kedarnath record provides compelling evidence for a reorganization of the global climate system taking place at 5.5 ka BP possibly after sea level stabilization and the advent of inter-annual climate variability governed by the modern ENSO phenomenon. The ISM record also captures warm-wet and cold-dry conditions during the Medieval Climate Anomaly and Little Ice Age, respectively.